Examining the impact of premenstrual dysphoric disorder (PMDD) on life and relationship quality: An online cross-sectional survey study - Sophie Hodgetts; Aaron Kinghorn (PLoS ONE, 2025)
Little is known regarding the impact of premenstrual dysphoric disorder (PMDD) on specific aspects of life quality within the home, such as spousal/partner relationships. Moreover, the impact of PMDD on the partners of those with the condition has not been investigated. Therefore, the present study examined the ways in which PMDD can affect the perceived life and relationship quality of both those with the condition, and their partners. Across two studies, cross-sectional survey methods were used to compare perceived quality of life and relationship quality between PMDD patients (n = 216) and controls (n = 187), and between PMDD partners (n = 92) and controls (n = 59). In both PMDD patients and their partners, perceived quality of life was lower across most domains compared to controls. Additionally, both PMDD patients and their partners reported lower relationship quality compared to controls, for all domains except love and commitment. Our findings indicate that PMDD has a wide-ranging impact on both the affected individual and their partner. Future clinical research should aim to develop PMDD-specific interventions that support both the person with PMDD and their partner.